Analysis of Symbolic Interactionism in Lontang Dance: Cultural Meaning and Social Dynamics in Purwaraja Village, Ciamis Regency - Apriani, Arni; Wasta, Asep; Husen, Wan Ridwan (JUPE : Jurnal Pendidikan Mandala, 2025)
Lontang Dance is a traditional Sundanese art form that developed in Purwaraja Village, Ciamis Regency, and functions as a medium for spiritual and social communication within the community. This study analyzes the symbolic meaning of Lontang Dance through the perspective of symbolic interactionism developed by George Herbert Mead and Herbert Blumer. Using a qualitative ethnographic approach, the study involved participant observation (n=32 participants), in-depth interviews with traditional figures and artists, and visual documentation. The analysis shows that cultural symbols such as the tray, seeng, and ibing movements in Lontang Dance are constructed through a dynamic and ongoing process of social interaction within the community. These symbolic meanings undergo modification and negotiation to maintain religious relevance without eliminating local cultural identity. These findings contribute to a deeper understanding of how cultural realities are constructed through human interaction and emphasize the importance of local cultural preservation in the context of modernization. This research opens new perspectives in the study of symbolic anthropology and local culture-based arts education.